CHARACTERISTICS OF STREET VENDORS IN THE TRANS-KALIMANTAN HANDIL BAKTI ROAD AREA - Dwina, Irma; Abbas, Ersis Warmansyah; Mutiani, Mutiani (JURNAL SOCIUS, 2024)
Street vendors play a crucial role in the local economy but are often overlooked due to the negative stigma surrounding their presence. Despite this, they view their work as honorable and contribute significantly to the welfare of the local community. This study aims to examine the characteristics of street vendors (PKL) in the Trans Kalimantan Handil Bakti Road area, a hub for trade activities due to its high accessibility and position as a crossroads between cities. A qualitative approach with a descriptive method was employed, and data were collected through observation, `interviews, and documentation. The findings reveal significant variations in the characteristics of street vendors, including: (1) Types of Commodities: Vendors offer a wide range of products, including ready-to-eat food, non-food items, and services. (2) Scale of Operations: The scale of operations is relatively large, driven by high traffic and vibrant local activity. (3) Location: The area is strategically positioned at an intercity crossroads, attracting both locals and travelers. (4) Distribution Patterns: Vendors typically follow an elongated distribution pattern along the road. (5) Nature of Operations: Most vendors fall into the categories of semi-sedentary and itinerant traders. (6) Operating Hours: Vendors usually begin trading around 3:00–4:00 PM and continue until midnight. These findings highlight the dynamic nature of street vending in this area, emphasizing its strategic importance and the diversity of services offered.